2019
DOI: 10.1039/c8ew00539g
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and fate of benzophenone-type UV filters in aquatic environments: a review

Abstract: Benzophenone-type ultraviolet filters (BP-type UV filters or BPs) are extensively used in a diverse array of personal care products (PCPs), including sunscreens and many cosmetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 121 publications
1
46
0
Order By: Relevance
“…Benzophenone-3 (BP3) is an organic UV filter commonly used in sunscreen formulations and other cosmetic products. Due to its widespread use, BP3 is now found in many environmental compartments such as freshwater and seawater, benthic sediments and aquatic biota (see Mao et al (2018) for a recent review).…”
Section: Introductionmentioning
confidence: 99%
“…Benzophenone-3 (BP3) is an organic UV filter commonly used in sunscreen formulations and other cosmetic products. Due to its widespread use, BP3 is now found in many environmental compartments such as freshwater and seawater, benthic sediments and aquatic biota (see Mao et al (2018) for a recent review).…”
Section: Introductionmentioning
confidence: 99%
“…The main role of sunscreens is to protect the skin against the harmful effects of ultraviolet (UV) radiation and their use is highly recommended to prevent sunburn and skin cancer [ 1 ]. The awareness of sunburn risk increased the consumption of cosmetics and sunscreens, particularly in coastal areas, promoting their spread into the aquatic environment [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that these compounds have the ability to bioaccumulate and biomagnify in the trophic chains of the aquatic ecosystems, with potential harmful effects for both the environment and wildlife [ 2 , 10 , 13 ]. Organic UV filters, such as camphor, salicylates and BP-3, are highly lipophilic [ 15 ], being rapidly bioaccumulated in aquatic organisms, such as corals, crustaceans, mussels and fish [ 1 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. BP-3 is partially metabolized and then excreted or accumulated in different fish tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Benzophenone-type UV lters are chemical substances used extensively in sunscreens and other personal care products such as body lotions, shampoos, lipstick and skin creams to protect lips, hair and skin against the solar irradiation (Mao et al, 2019). Due to their extensively applications, organic UV lters and their metabolites may be released into environment through human activities or through wastewater treatment plant e uent discharges, which are not always capable of completely remove these micropollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their extensively applications, organic UV lters and their metabolites may be released into environment through human activities or through wastewater treatment plant e uent discharges, which are not always capable of completely remove these micropollutants. In recent years, many studies reported the presence of organic UV lters, including 2-hydroxy-4-methoxy-benzophenone (BP-3), 4-hydroxibenzophenone (4-HBP) and 2,4-dixydroxybenzophenone (BP-1), in concentration levels ranging from nanograms per liter to microgram per liter in surface waters and sediments (Chiriac et al, 2021;O'Malley et al, 2021;Fagervold et al, 2019;Apel et al, 2018;Tsui et al, 2019;Mitchelmore et al, 2019), wastewaters and sewage sludge (Chiriac et al, 2021;Wu et al, 2018;Mao et al, 2019;O'Malley et al, 2019). The major concern regarding these chemical compounds is related to the easiness with which they can bioaccumulate in living organisms, especially due to the negative properties they can have: alter sex hormonal balance, affect endocrine signaling and impede reproductive capacity.…”
Section: Introductionmentioning
confidence: 99%